Spontaneous spinal epidural hematoma with hemiparesis: A stroke mimic - Mio Suzuki; Yasuhiro Kano; Satoshi Watanuki; Kengo Murata (Clinical Case Reports)
Key Clinical Message Spontaneous spinal epidural hematoma (SSEH) is a rare cause of neck pain and hemiparesis. Clinicians should keep SSEH in mind as a rare stroke mimic presenting with hemiparesis to avoid needless and potentially hazardous thrombolytic therapy. Taking a careful history is useful for making a correct diagnosis.